Pengaruh Faktor Psikososial Dan Cara Persalinan Terhadap Terjadinya Post Partum Blues Pada Ibu Nifas (Studi di Ruang Nifas RSUD R.A Bosoeni Mojokerto) - Dian Irawati Farida Yuliani; Farida Yuliani (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2014)
Postpartum blues or postpartum mental disorders are many found and not treated properly. The objectives of this study is to determine the effect of psychosocial factors (age, parity, education, knowledge, husband support, socio- economic, marital status, pregnancy status) on the postpartum blues. So the healthcare provider can treat postpartum blues considered by maternal psychosocial factors. Assessment of psychosocial factors indicate that the treat of postpartum blues not only depend on mothers and health care provider but of all the families. The multisectoral traetment will prevent postpartum depression and decreasing the incidence of psychosis in the mother and child . This study designed by cross-sectional design. Samples taken by random sampling. Samples of this study as many as 37 respondents who given birth at RA Basoeni Hospital, Mojokerto. By using observation and structured interviews, research was held on June 7 to 18 October 2013. Variables of this study are age, parity, education, knowledge, husband support, socio- economic, marital status, pregnancy status, and postpartum blues. The results showed the majority of respondents aged < 20 years and > 35 years, with a high education, had married, has a high socioeconomic, multiparous, unwanted pregnancy status, no husband support, lack of knowledge, sectio caesarea, and more than 50 % of respondents get postpartum blues. Using by the logistic regression, the results showed that the effect on the incidence of postpartum blues are age, parity, educational level, husband support, pregnancy status, and knowledge (p value < 0.05) . The holistic treatment is important to decrease incidence of postpartum blues. Early detection or screening should be a routine assessment in postpartum mothers. Healthcare provider should be considerate to the presence of depressive symptoms in postpartum mothers.